(untitled) (Fiep Bulletin - online, 2015)
In 1961, henry Steele Commager, the noted Amherst historian, enumerated what he considered to be the advances made in the world in the last quarter century. Despite a great deal of evil, he felf that the forces of good had gone steadfastly ahead.